PERBEDAAN ABNORMAL RETURN SEBELUM DAN SESUDAH KENAIKAN HARGA BAHAN BAKAR MINYAK 2005 - Mardiana, Lilik (Research Institution and Community Service Wijaya Kusuma Surabaya University, 2006)
Increasing fuel price is interested phenomenon. Increasing fuel price has information content that affect the market. Market will be negative to respon increasing fuel price. This studies examines whether abnormal return difference or not difference before and after increasing fuel price. The analysis unit are 45 companies registered on the Jakarta Stock Exchange in September-Oktober 2005. The hypothetical test was tested by paired sample t test. The result proved that abnormal return decreased after increasing fuel price.